1991
DOI: 10.1007/bf00228518
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of noradrenergic ascending pathways in the stress-induced activation of ACTH and corticosterone secretions is dependent on the nature of stressors

Abstract: The aim of the present study was to explore in male rats the role of the catecholaminergic innervation of the hypothalamus in corticotropic and adrenal responses to different kinds of stress conditions. For this purpose, 6-hydroxydopamine (3 micrograms in 0.2 microliter saline) was stereotaxically and bilaterally infused at two levels of the main noradrenergic ascending brain stem bundle (NAB-X). The efficiency of catecholaminergic denervation of the hypothalamus was checked by measuring noradrenaline concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…However, previous studies showed middle-aged related differences in plasmatic CORT or corticotropin-releasing factor responses to different types of stress when compared to young animals (Nolan et al, 1991;Pisarska et al, 2000). Reports of increased CORT levels for 3 days post-stress exist (Gaillet et al, 1991;Ottenweller et al, 1994), however, in most cases, the plasmatic CORT response corresponds to a transitory peak occurring within the first 30 min post (stress) stimulus (Xu et al, 1997). Our experiments showed that the CORT release was significantly increased 30 min but not 5 or 24 hours following fear conditioning, while acute GSM exposure alone did not affect CORT in young adults.…”
Section: Gsm Exposure Stress and Emotional Memorymentioning
confidence: 92%
“…However, previous studies showed middle-aged related differences in plasmatic CORT or corticotropin-releasing factor responses to different types of stress when compared to young animals (Nolan et al, 1991;Pisarska et al, 2000). Reports of increased CORT levels for 3 days post-stress exist (Gaillet et al, 1991;Ottenweller et al, 1994), however, in most cases, the plasmatic CORT response corresponds to a transitory peak occurring within the first 30 min post (stress) stimulus (Xu et al, 1997). Our experiments showed that the CORT release was significantly increased 30 min but not 5 or 24 hours following fear conditioning, while acute GSM exposure alone did not affect CORT in young adults.…”
Section: Gsm Exposure Stress and Emotional Memorymentioning
confidence: 92%
“…This result is difficult to explain at this stage because, to the best of our knowledge, this study is the first to report any effect of hypoxia on circulating estradiol levels. Functional analysis of neuroanatomical pathways linking the brain stem nuclei that receive synaptic inputs from the peripheral chemoreceptors to hypothalamic regions regulating hormone release (17,33) would likely help explain how housing had such dramatic effects on this response. That the hypoxic response pattern for testosterone was similar suggests that similar mechanisms may be involved.…”
Section: Interactions Between Gonadotropic and Corticotropic Axes Andmentioning
confidence: 99%
“…Blood was immediately centrifuged and the resulting plasma was kept at -20°C until ACTH assay. Restraint stress was performed for 2 h by wrapping the body of the rat in Elastoplast as previously described (Gaillet, Lachuer, Malaval, Assenmacher & Szafarczyk, 1991). LPS (Escherichia coli Serotype 055:B5, Sigma; 1 /tg (kg body weight)-1 diluted in 150 #u1 normal saline) was injected via the arterial cannula for 15-20 s. At the end of the experiment animals were decapitated and brains were removed and frozen.…”
Section: Methodsmentioning
confidence: 99%